Depression mediates the relationship between social capital and health‐related quality of life among Chinese older adults in the context of the COVID‐19 pandemic: A cross‐sectional study - Ping Zhang; Xiao‐Li Liu; Rong‐Mei Zhang; Ning Xia (Wiley, 2023)
Abstract Aim To explore the association between social capital and health‐related quality of life (HRQoL) and to determine whether depression mediates the association among Chinese older adults in the context of the COVID‐19 pandemic. Design A descriptive cross‐sectional research design. Methods The Geriatric Depression Scale‐15, Social Capital Questionnaire and 12‐item Short‐Form Health Survey were used to investigate 1201 older adults selected from Jinan, Shandong Province, China, using a multistage stratified cluster random sampling method. Results Pearson's correlation analysis revealed a significant positive correlation between social capital and HRQoL (r = 0.269, p < 0.01). Multivariate linear regression analyses demonstrated that social capital was significantly negatively associated with depression (β = −0.072, p < 0.001) and that depression was associated with HRQoL (β = −1.031, p < 0.001). The mediation analyses showed that depression mediated the association between social capital and HRQoL, and the indirect effect size was 0.073 (95% confidence interval: 0.050, 0.100).